STUDIES OF GALACTIC CEPHEIDS: THE INASAN/SAI INTEGRATED PROGRAM - Samus, N. N.; Antipin, S. V.; Berdnikov, L. N.; Dambis, A. K.; Gorynya, N. A.; Rastorguev, A. S. (Одеські астрономічні публікації, 2007)
We present the review of the main results of more than two decades of the Moscow program of Cepheid studies, carried out at the Institute of Astronomy (INASAN) and Sternberg Astronomical Institute (SAI). This program consists of extensive photometry and radial velocity measurements (the contribution from our team being the largest among observations of comparable precision), studies of period variations (permitting identification of the number of a particular star's current instability-strip crossing), detection of spectroscopic binaries among Cepheids, determinations of Cepheid radii, discoveries of double-mode Cepheids, studies of galactic structure, kinematics, and dynamics, etc.